Comparison of time to death and its predictors among hospitalized children with and without severe acute malnutrition at Mulanje District Hospital, Southern Malawi - Masuzgo Rodney Pajogo; Miriam Ndholvu (PLoS ONE, 2025)
Introduction Severe acute malnutrition (SAM) is a major cause of child mortality in sub-Saharan Africa, yet recent data from Mulanje District Hospital, Malawi, showed higher mortality among non-SAM under-five children. This unexpected trend highlights a knowledge gap, as no studies in Malawi have compared time to death and its predictors between SAM and non-SAM children. This study aimed to fill that gap by examining and comparing mortality timing and predictors in both groups. Methods A retrospective cohort study was conducted using medical records of 454 randomly selected under-five children admitted to Mulanje District Hospital between January 2017 and February 2021. Data were collected using structured forms and analysed in STATA version 16. Cox proportional hazards regression was used to identify mortality predictors, with significance set at p < 0.05. Results The overall mortality rate was 14.8%, with higher mortality in non-SAM children (21.2%) than SAM children (8.4%). The median time to death was 5 days (IQR: 2–8) for SAM and 1 day (IQR: 1–2) for non-SAM children. Among SAM children, not having received amoxicillin (AHR: 4.59; CI: 1.46–14.43) was a significant predictor of death. Among non-SAM children, facility referral (AHR: 2.66 (95% CI: 1.34–5.27)), oxygen therapy (AHR: 4.04 (95% CI: 2.11–7.71)), and not having received amoxicillin (AHR: 33.49 (95% CI: 4.47–250.7)) were significant predictors of mortality. Conclusion The higher mortality observed among non-SAM children reflected more acute disease presentations and delays in effective intervention, underscoring the need for rapid triage and treatment in this group.